ChemInform Abstract: Synthesis of Heterocycles via Palladium‐Catalyzed C—H Activation/Cyclization of Diazonium Salts. Part 3. Phenanthridin‐6‐(5H)‐ones. Issue 8 (February 2015) - Du, Zhen‐Ting; Han, Pan; Zhou, Jing; Zhang, Cong‐Cong; Chen, Ke
Abstract Optimum reactions are examined for the synthesis of 17 phenanthridin‐6‐(5H)‐ones (II) by palladium‐catalyzed cyclization of diazonium salts (I).